Chemical environment of an acidic Hibiscus sabdariffa beverage and its role in early amylolytic interactions in a starch-based food system - Sofia Guadalupe Chairez-Huerta; José P. Tejeda-Miramontes; Alicia Paulina Cárdenas-Castro; Edgar J. Mendivil; Jorge Alberto Sánchez-Burgos; Sonia Guadalupe Sáyago-Ayerdi (Food Research International, 2026)

Chemical composition of fine particulate matter and all-cause mortality of older lung cancer patients - Yaguang Wei; Jiaowei Gong; Edgar Castro; Min Zhang; Robert O. Wright; Christine C. Ekenga; Joel D. Schwartz (Environmental Research, 2026)

Functional venom activity and antivenom neutralization in rattlesnakes across Baja California and Gulf of California islands - Samuel R. Hirst; Edgar Neri-Castro; Emiliano Vázquez-García; Vanessa Zarzosa; Felipe Olvera; Cameron M. VanHorn; Alejandro Alagón; Hector Franz-Chávez; Gamaliel Castañeda-Gaytán; Christopher L. Parkinson; Jason L. Strickland; Miguel Borja; et al. (Toxicon, 2026)

Effects of pRmS-17-specific antibodies on reproductive performance and tissue integrity of Rhipicephalus microplus - Edgar Castro-Saines; Dulce María Galván-Arellano; Raúl Fajardo; Rodolfo Lagunes-Quintanilla (Veterinary Parasitology, 2026)

Lead and cadmium in raw milk from family-based dairy systems in the central highlands of Peru: Implications for physicochemical composition and potential health risk - Doris Chirinos-Peinado; Jorge Castro-Bedriñana; Eustace Barnes; Edgar García-Olarte; Gianfranco Castro-Chirinos; Aracely Atachagua-Munguía; Elizabeth Escobar-Caballón; Mayra García-Crisóstomo; Mayumi Huamán-Carhuamaca; Franco Millán-Quiñones; María Misayauri-Castro; Albert Torres-Huamanchaqui; et al. (Next Research, 2026)

Arbuscular mycorrhizal fungi and bacterial communities across selective logging, low-flooded forest and conserved Mayan Forest - Carlos Alberto Puch-Hau; Martin Hassan Polo-Marcial; Bruno Tomio Goto; Mercedes Amparo Quintanilla-Mena; Mayra Alejandra Cañizares-Martínez; Diana E. Adame-Castro; Brisni Z. Pérez-Garfias; Alfredo F. Yanez-Montalvo; Silvia G. Granados-Puerto; Edgar González-Godoy; Magdalena Márquez-Santos; Luis Alberto Lara-Pérez (Applied Soil Ecology, 2026)

Translational medicine protocol for proteomics clinical research on snakebite envenoming: contributions for develop studies in mechanisms and new biomarkers - Joeliton S. Cavalcante; Juliana Sartorelo Almeida; João Victor C. Coutinho; Edgar E. Neri Castro; Manuela B. Pucca; Alejandro Alagón; Rui Seabra Ferreira Junior (Archives of Toxicology, 2026)

Neurotoxic snake venoms in Mexico: Diversity and recent advances - Edgar Neri-Castro (Toxicon, 2026)

Essential oils as an alternative control against cattle ticks in México: an integrative review - Edgar Castro-Saines; Jair Millán-Orozco; Germán Román Colmenares-Viladomat; Elizabeth Salinas-Estrella; Christian Carreño-Campos; Jorge A. Maldonado-Jáquez; Liliana Aguilar-Marcelino (Experimental and Applied Acarology, 2025)

Corn and bean in an agroforestry system: growth, yield, and efficiency of solar radiation interception - Valeria Pohlmann; Edgar Ricardo Schöffel; Eberson Diedrich Eicholz; Ernestino de Souza Gomes Guarino; Gustavo Rodrigues Scheer; Eduarda Voigt Franz; Frederico de Castro Mayer (Agroforestry Systems, 2025)

Chronic effects of wildfire smoke and criteria air pollutants on cardiovascular hospitalization rates in the contiguous US - Cheng Jin; Mahdieh Danesh Yazdi; Hanbing He; Edgar Castro; Joel D. Schwartz; Robert O. Wright; Yaguang Wei (Environmental Research, 2025)

Cytotoxic activity of the crude venom from Odontomachus affinis ants is mediated by thiol oxidation and mitochondrial dysfunction - Jorge Luis Maria Ruiz; Vyctória dos Santos Ramos; Débora Cristina de Oliveira Gonçalves; Thamires Regine Corga da Silva Angelo; Priscila dos Santos Pazini; Ricardo José Soares Torquato; Wagner Alves de Souza Júdice; Antonio Miranda; Edgar Julian Paredes-Gamero; Maria Santina de Castro Morini; Tiago Rodrigues (Toxicon, 2025)

Tailored toxins: Coagulotoxic variations in Atropoides, Cerrophidion, Metlapilcoatlus, and Porthidium viperid venoms against diverse vertebrate plasmas - Lee Jones; Edgar Neri-Castro; Nicholas J. Youngman; Joshua Llinas; Mark Haworth; Amber Gillett; Bryan G. Fry (Toxicon, 2025)

Relationship between the distribution of rare earth elements in soil pools with plant uptake: a sequential extraction study - Kaisa Forsyth; Aline Dia; Rosa Marques; Maria Isabel Prudêncio; Cynthia Obregón-Castro; Catarina Diamantino; Edgar Carvalho; Maxime Pattier; Mélanie Davranche; Mathieu Pédrot (Plant and Soil, 2025)

PD-based ADRC using time-varying gains: An application to microalgal-based bioprocess - Viyils Sangregorio-Soto; Edgar Yesid Mayorga Lancheros; Gianfranco Mazzanti; Claudia L. Garzón-Castro (Journal of Theoretical Biology, 2025)

Effective novel and conventional technologies for decontamination of aflatoxin B1 in foods: a review - Diego Fernando García-Ramón; Heber P. Cornelio-Santiago; Edgar Norabuena; Liliana Sumarriva; Hermelinda Alvarez-Chancasanampa; Marlitt Naupay Vega; Alejandrina Sotelo-Méndez; Luis Alfredo Espinoza-Espinoza; Lucia R. Pantoja-Tirado; Sara H. Gonzales-Agama; Esmila Y. Chavarría-Marquez; Cesar Raul Castro-Galarza (Mycotoxin Research, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Venom variation and ontogenetic changes in the Crotalus molossus complex: Insights into composition, activities, and antivenom neutralization - Miguel Borja; Gamaliel Castañeda-Gaytán; Alejandro Alagón; Jason L. Strickland; Christopher L. Parkinson; Areli Gutiérrez-Martínez; Bruno Rodriguez-López; Vanessa Zarzosa; Bruno Lomonte; Anthony J. Saviola; Julián Fernández; Cara F. Smith; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Taking the sting out of scorpions: Electrophysiological investigation of the relative efficacy of three antivenoms against medically significant Centruroides species - Sam I.D. Campbell; Chun Yuen Chow; Edgar Neri-Castro; Alejandro Alagón; Aarón Gómez; Raúl Soria; Glenn F. King; Bryan G. Fry (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Fangs and foliage: Unearthing the haemotoxic secrets of cannabis-dwelling rattlesnakes - Lachlan A. Bourke; Christina N. Zdenek; Tam M. Huynh; Wayne C. Hodgson; Alejandro Alagón; Edgar N. Castro; Jason Jones; Bryan G. Fry (Toxicon, 2024)

Long-term exposure to PM2.5 species and all-cause mortality among Medicare patients using mixtures analyses - Mahdieh Danesh Yazdi; Heresh Amini; Yaguang Wei; Edgar Castro; Liuhua Shi; Joel D. Schwartz (Environmental Research, 2024)

Quantifying venom production: A study on Micrurus snakes in Mexico - Edgar Neri-Castro; Vanessa Zarzosa; Melisa Benard-Valle; Audrey Michelle Rodríguez-Solís; Lorena Hernández-Orihuela; Javier A. Ortiz- Medina; Alejandro Alagón (Toxicon, 2024)

Long-term noise exposures and cardiovascular diseases mortality: A study in 5 U.S. states - Tingfan Jin; Anna Kosheleva; Edgar Castro; Xinye Qiu; Peter James; Joel Schwartz (Environmental Research, 2024)

Green synthesis of ZnO nanoparticles from ball moss (Tillandsia recurvata) extracts: characterization and evaluation of their photocatalytic activity - Nayeli Fabiola Ibarra-Cervantes; Edgar Vázquez-Núñez; Christian Gómez-Solis; Fabian Fernández-Luqueño; Gustavo Basurto-Islas; Jonathan Álvarez-Martínez; Rigoberto Castro-Beltrán (Environmental Science and Pollution Research, 2024)

Air quality disparities mapper: An open-source web application for environmental justice - Ethan McFarlin; Falco J. Bargagli-Stoffi; Edgar Castro; Joel Schwartz; Francesca Dominici; Heresh Amini (Environmental Modelling & Software, 2024)

Geochemical Behaviour of Rare Earth Elements Throughout an Acid Mine Drainage Passive Treatment System in the Lousal Mine Area, Portugal - Cynthia Obregón-Castro; Maria Isabel Prudêncio; Catarina Diamantino; Edgar Carvalho; Dulce Russo; Rosa Marques (Mine Water and the Environment, 2023)
A passive remediation system was installed between 2010 and 2015 at the Lousal legacy mine site in southwestern Portugal to minimize the impact of AMD. This is the first study of the geochemical behaviour of rare earth elements (REE) in the area after implementation of the passive treatment system. The total and dissolved concentrations of REE is similar throughout the basins/wetlands and acidic ponds in both sampling campaigns, which is mainly attributed to the conservative behaviour of these elements in acidic water. In areas where mixing of acidic and circumneutral water occurs, the REE were partially removed from solution by adsorption onto newly formed Al and Fe precipitates. Sorption onto the precipitates varies between the rare earths, with a preferential fixation of heavy REE (HREE) compared to the light REE (LREE). The normalized distribution patterns exhibit the characteristic convex-up enrichment in middle rare earth elements for AMD and display an enrichment of LREE relative to HREE in areas where mixing of waters occurs, and the pH is close to circumneutral.

Ontogenetic change in the venom composition of one Mexican black-tailed rattlesnake (Crotalus molossus nigrescens) from Durango, Mexico - Miguel Borja; Edgar Neri-Castro; Arelí Gutiérrez-Martínez; Richard Bledsoe; Vanessa Zarzosa; Bruno Rodriguez-López; Jason L. Strickland; Jorge Becerra-López; Sara Valenzuela-Ceballos; Christopher L. Parkinson; Alejandro Alagón; Gamaliel Castañeda-Gaytán (Toxicon, 2023)

Socioeconomic and racial disparities in source-apportioned PM2.5 levels across urban areas in the contiguous US, 2010 - Pablo Knobel; Inhye Hwang; Edgar Castro; Perry Sheffield; Louisa Holaday; Liuhua Shi; Heresh Amini; Joel Schwartz; Maayan Yitshak Sade (Atmospheric Environment, 2023)

Air pollution, climate conditions and risk of hospital admissions for psychotic disorders in U.S. residents - Xinye Qiu; Yaguang Wei; Marc Weisskopf; Avron Spiro; Liuhua Shi; Edgar Castro; Brent Coull; Petros Koutrakis; Joel Schwartz (Environmental Research, 2023)

Histometric and morphological damage caused by Serratia marcescens to the tick Rhipicephalus microplus (Acari: Ixodidae) - Edgar Castro-Saines; Guadalupe Peña-Chora; Claudia Hallal-Calleros; Rodolfo Lagunes-Quintanilla; Ivan Flores-Perez; Ruben Hernandez-Ortiz (Archives of Microbiology, 2022)

Genome analysis of Pseudomonas sp. 14A reveals metabolic capabilities to support epiphytic behavior - Saúl Alejandro Medina-Salazar; Fernanda Cornejo-Granados; Edgar Equihua-Medina; Adrian Ochoa-Leyva; Moisés Roberto Vallejo-Pérez; Delia Xochil Vega-Manriquez; Ramón Jarquin-Gálvez; Rigoberto Castro-Rivera; Gisela Aguilar-Benítez; José Pablo Lara-Ávila (World Journal of Microbiology and Biotechnology, 2022)

BoaγPLI from Boa constrictor Blood is a Broad-Spectrum Inhibitor of Venom PLA2 Pathophysiological Actions - Caroline Fabri Bittencourt Rodrigues; Christina N. Zdenek; Caroline Serino-Silva; Karen de Morais-Zani; Kathleen Fernandes Grego; Melisa Bénard-Valle; Edgar Neri-Castro; Alejandro Alagón; Anita Mitico Tanaka-Azevedo; Bryan Grieg Fry (Journal of Chemical Ecology, 2021)

Characterization of a strain of Serratia sp. with ixodicide activity against the cattle tick Rhipicephalus microplus - Edgar Castro-Saines; Ruben Hernandez-Ortiz; Rodolfo Lagunes-Quintanilla; Guadalupe Peña-Chora (Experimental and Applied Acarology, 2021)

Chronic stress decreases ornithine decarboxylase expression and protects against 1,2-dimethylhydrazine-induced colon carcinogenesis - Edgar Oswaldo Zamora-González; Patricia Castro-Félix; María del Rosario Huizar-López; Josefina Casas-Solís; María de la Luz Blanca Isabel Marques-González; Martha Fabiola Martin del Campo-Solís; Anne Santerre (Molecular Biology Reports, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Chloroplast and nuclear ribosomal cistron phylogenomics in a group of closely related sections in Salvia subg. Calosphace - Edgar I. Olvera-Mendoza; Grant T. Godden; Juan Carlos Montero-Castro; J. Mark Porter; Sabina I. Lara-Cabrera (Brazilian Journal of Botany, 2020)

First report of root and crown rot caused by a member of Phytophthora clade 9 on Carica papaya in Mexico - Santo Ángel Ortega-Acosta; Francisco Palemón-Alberto; Guadalupe Reyes-Garcia; Carlos Alberto Nuñez-Colín; Jesús Rubén Rodríguez-Nuñez; Porfirio Juarez-López; Edgar Espinosa-Trujillo; Alfredo Josué Gámez-Vázquez; Elías Hernández-Castro; Pablo Rufino-Marcelino (Journal of Plant Pathology, 2020)

Mutational landscape and intra-host diversity of human papillomavirus type 16 long control region and E6 variants in cervical samples - Noé Escobar-Escamilla; Blanca Estela González-Martínez; Adnan Araiza-Rodríguez; David Esaú Fragoso-Fonseca; Abraham Pedroza-Torres; Magaly Guadalupe Landa-Flores; Fabiola Garcés-Ayala; Edgar Mendieta-Condado; José Alberto Díaz-Quiñonez; Graciela Castro-Escarpulli; José Ernesto Ramírez-González (Archives of Virology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Multi-environment multi-QTL association mapping identifies disease resistance QTL in barley germplasm from Latin America - Lucia Gutiérrez; Silvia Germán; Silvia Pereyra; Patrick M. Hayes; Carlos A. Pérez; Flavio Capettini; Andres Locatelli; Natalia M. Berberian; Esteban E. Falconi; Rigoberto Estrada; Dario Fros; Victor Gonza; et al. (Theoretical and Applied Genetics, 2015)

High rate of detection of G8P[6] rotavirus in children with acute gastroenteritis in São Tomé and Príncipe - Claudia Istrate; Sumit Sharma; Johan Nordgren; Sandra Videira e Castro; Ângela Lopes; João Piedade; Ahmed Zaky; António Lima; Edgar Neves; José Veiga; Aida Esteves (Archives of Virology, 2015)